Transcriptomic Analysis of Pathogenicity Genes in Sclerotinia sclerotiorum Affecting Brassica napus - Hengameh Taheri; Mohamad Hamed Ghodoum Parizipour (Journal of Genetic Resources)
Sclerotinia stem rot (SSR) caused by Sclerotinia sclerotiorum is one of the most destructive diseases of rapeseed (Brassica napus L.) globally. This study identifies key genes involved in the pathogenicity of S. sclerotiorum during rapeseed infection. It examines these genes' codon usage bias (CUB) to find the optimal codons effective in gene expression and the factors effective in the formation of CUB. Protein-protein interaction network was drawn and several hub genes were determined and ranked according to the CytoHubba tool among which the genes encoding nitrate reductase, beta-glucosidase, glucanase, PA14 domain-containing protein, carbohydrate-binding module family 1, and acyl-coenzyme A oxidase were found to be associated with the SSR induction. Gene ontology (GO) analysis showed that the genes related to the metabolism of organic substances, catalytic activity, and cellular anatomical entity had the highest count. Also, KEGG pathways analysis revealed 16 biological pathways modulated by S. sclerotiorum among which the genes associated with the metabolic pathways exhibited the highest count. CUB indices including CAI (codon adaptation index), ENC (effective number of codons), GC, GC3S (GC content in the third open position of the codon), and RSCU (relative synonymous codon usage) were determined and the results showed a significant positive correlation between GC and GC3S. Also, the possible effects of mutation pressure and natural selection in shaping CUB were determined. The mean ENC range from 42.4-56.65 indicating less orientation in codon usage. The range CAI was found to be 0.74-0.89 indicating the importance of genes in adapting to environmental stresses. The maximum RSCU was 1.76 for the CCA codon, which encodes the amino acid (aa) proline with a high preference for that codon compared to other synonymous codons of that aa. These results demonstrated that S. sclerotiorum modulates some genes involved in disease induction (e.g., cell wall-degrading enzymes, biosynthesis of secondary metabolites & metabolic pathways) to infect its host plant.